Undifferentiated hepatic carcinoma with osteoclast-like giant cells: A case report and literature review - Deng, Yujiao; Wang, Ya; Zhang, Yan; Yang, Na; Ji, Xingli; Wu, Bing (Frontiers in Oncology, 2023)
Osteoclast-like giant cell tumor (OGCT) is a common bone tumor, occasionally observed in some extraosseous organs, but rarely involving the digestive system, especially the liver. Previously reported osteoclast-like giant cell carcinoma of the liver often coexists with sarcomatoid or hepatocellular carcinoma. Undifferentiated liver tumors with osteoclast-like giant cells (OGCs) are extremely rare. Due to its rarity, there is no consensus for diagnosis and treatment of undifferentiated liver tumors with OGCs. Definitive diagnosis comes from surgery, so there is often a long delay in diagnosis following the occurrence of symptoms. This case describes an extremely rare case of an undifferentiated liver tumor with OGCs in detail. It also summarizes the previously published cases based on liver tumors with OGCs from August 1980 to June 2021, providing extensive evidence to improve preoperative diagnosis and management options.